Author Correction: A computerized diagnostic model for automatically evaluating placenta accrete spectrum disorders based on the combined MR radiomics-clinical signatures - Hao Zhu; Xuan Yin; Haijie Wang; Yida Wang; Xuefen Liu; Chenglong Wang; Xiaotian Li; Yuanyuan Lu; Guang Yang; He Zhang (Scientific Reports, 2022)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.